Implementasi Pembelajaran Pendidikan Agama Islam Menggunakan Aplikasi Cerdas Cermat Islami Di SDN Jatisari IV Pasuruan - Muzammil Adiputro (4, 2025)
This research is motivated by students' low interest and understanding of Islamic Religious Education (PAI), which has been dominated by monotonous lecture methods and minimal innovation in learning media. In today's digital era, elementary school students are already very familiar with technological devices such as smartphones, opening up opportunities for teachers to utilize digital media as learning aids. This study aims to describe the implementation of Islamic Religious Education (PAI) learning using the